Role of a dentist in environment protection-A short communication - M Nazargi Mahabob (International Journal of Oral and Craniofacial Science - Peertechz Publications, 2021)
When we turn on either news channels or social media, we can see the interesting news about plans of colonizing Mars or other planets. However, at the same time it also mentioning the difficulties, uncertainties and cost of the projects. All these because Earth is the only known and proven planet is having liveable environment in the Universe. An environment is the natural surroundings that help living things to grow, develop and nourish naturally and determines our existence on the planet possible. What we are using for our own existence is coming from the environment. If the stability of the environment disturbed, the very own existence of the life will become questionable. One of most affecting thing to the environment stability is pollution.